RESPON PERTUMBUHAN TANAMAN JENGKOL DAN NANGKA TERHADAP PEMUPUKAN DI BLOK GARUNG TAMAN NASIONAL GUNUNG HALIMUN SALAK: Growth Response of Jengkol and Jackfruit Plants to Fertilization in the Garung Block of Mount Halimun Salak National Park (Jurnal ForestrIndo, 2025)
One of the conservation partnership areas in Mount Halimun Salak National Park (MHSNP) is the Cikaniki Sejahtera Forest Farmers Group (KTH), which does not yet have any forestry crops. The Forest and Land Rehabilitation Program (RHL) is carried out through an agroforestry system with support from Japan International Forestry Promotion and Cooperation Center (JIFPRO). This study aims to analyze the effect of NPK fertilizer and ecoenzyme on the growth of jengkol and jackfruit plants. The study was conducted using a factorial completely randomized design (CRD), namely NPK fertilizer doses (0; 2.5; and 5 g), ecoenzyme fertilizer concentration (0; 10; and 20 ml/L), and a combination of NPK fertilizer and ecoenzyme. The results showed that the use of 10 ml/L ecoenzyme fertilizer had a very significant effect on the height and stem diameter of jengkol plants. In jackfruit plants, the use of 5 g NPK fertilizer and 10 ml/L ecoenzyme fertilizer individually had a very significant effect on height growth.